Identification of Drought-tolerant Local Cowpea Varieties of Southwest Maluku (Indonesia) - Karuwal, Ritha Lusian; Suharsono, Suharsono; Tjahjoleksono, Aris; Hanif, Novriyandi (UI Scholars Hub, 2018)
Cowpeas grown in Southwest Maluku have local potential due to their diversity and ability to adapt to drought stress conditions that otherwise cause low productivity. The purpose of this study was to identify of local cowpea varieties of Southwest Maluku that show tolerance to drought. The experimental samples were seven local varieties and threereference cultivars. The drought stress treatment was altered watering periods, i.e., every two (P0) and ten days (P1) from growth to harvest. The results of this research showed that a ten-day watering period significantly decreased plant height, number of leaves, number of root nodules, root and shoot dry weight, photosynthesis rate, stomatal conductance, transpiration rate, relative water content, media water content, chlorophyll content, and number and weight of seeds perplant. Drought stress treatment increased proline content and root length. Correlation analysis showed a significant correlation between plant height with all variables, except for root length, proline content, and weight of seedsper plant. The correlation and cluster analyses showed that the KM7 variety is a drought tolerant genotype among the local cowpea varieties from Southwest Maluku. Therefore, the KM7 variety can be used as plant material in future breeding programs.